2016
DOI: 10.1016/j.yrtph.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Tobacco Heating System 2.2. Part 6: 90-day OECD 413 rat inhalation study with systems toxicology endpoints demonstrates reduced exposure effects of a mentholated version compared with mentholated and non-mentholated cigarette smoke

Abstract: The toxicity of a mentholated version of the Tobacco Heating System (THS2.2M), a candidate modified risk tobacco product (MRTP), was characterized in a 90-day OECD inhalation study. Differential gene and protein expression analysis of nasal epithelium and lung tissue was also performed to record exposure effects at the molecular level. Rats were exposed to filtered air (sham), to THS2.2M (at 15, 23 and 50 μg nicotine/l), to two mentholated reference cigarettes (MRC) (at 23 μg nicotine/l), or to the 3R4F refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 59 publications
5
27
0
Order By: Relevance
“…Exposure of the female rats to nicotine-containing aerosols resulted in numerically higher absolute and relative ovary weights, although the differences were mainly statistically significant after normalization to brain weights (p ≤ 0.05). Exposure to nicotine that resulted in lower uterus weights and higher ovary weights in the rats in the current study was also reported after 90 days of exposure in response to conventional cigarettes and heated tobacco sticks (Oviedo et al 2016;Phillips et al 2018;Wong et al 2016) and by others (Iranloye and Bolarinwa 2009;Patil et al 1999). High absolute and relative testis weights were noticed in males following exposure to nicotine, but the differences were only significant when testis weights relative to body weights were compared with rats in the reference groups (non-flavored and no-nicotine aerosols) as well as between rats in the high flavored e-liquid concentration and PBS control groups (both p ≤ 0.05).…”
Section: Effects On Non-respiratory Organssupporting
confidence: 83%
See 1 more Smart Citation
“…Exposure of the female rats to nicotine-containing aerosols resulted in numerically higher absolute and relative ovary weights, although the differences were mainly statistically significant after normalization to brain weights (p ≤ 0.05). Exposure to nicotine that resulted in lower uterus weights and higher ovary weights in the rats in the current study was also reported after 90 days of exposure in response to conventional cigarettes and heated tobacco sticks (Oviedo et al 2016;Phillips et al 2018;Wong et al 2016) and by others (Iranloye and Bolarinwa 2009;Patil et al 1999). High absolute and relative testis weights were noticed in males following exposure to nicotine, but the differences were only significant when testis weights relative to body weights were compared with rats in the reference groups (non-flavored and no-nicotine aerosols) as well as between rats in the high flavored e-liquid concentration and PBS control groups (both p ≤ 0.05).…”
Section: Effects On Non-respiratory Organssupporting
confidence: 83%
“…Histopathological evaluation revealed minimal lymphoid atrophy in both sexes from all groups, and this change was considered stress-related, as the thymus is the lymphoid organ most sensitive to stress (Everds et al 2013). A similar effect was observed in previous 90-day rat inhalation studies (Oviedo et al 2016;Phillips et al 2017;Wong et al 2016), where lower thymus weights were detected in rats exposed to nicotine-containing aerosols, although not in a concentrationdependent manner. The findings were no longer observed after the recovery period.…”
Section: Systemic Stress Responsessupporting
confidence: 82%
“…The tobacco industry has performed multiple studies regarding health consequences of HTP use. The results of in vitro and in vivo studies indicate that HTP aerosols have lower toxicity and no new hazards compared to conventional cigarette smoke [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The results of humanbased studies also suggest that switching from conventional cigarettes to IQOS or glo leads to reductions in exposure to smoke toxicants in a manner comparable to quitting tobacco use [74][75][76][77][78].…”
Section: Marketing Strategies Of Htp Promotionmentioning
confidence: 95%
“…Following the manufacturer recommendations, especially proper cleaning of the device after each 20 tobacco sticks seems to be crucial to provide proper thermal regulation and reduce emissions of harmful substances. Most of the research regarding the chemical composition of generated aerosol was carried out on brand new, never used devices [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Independent researchers showed that the use of 1 IQOS tobacco stick left a significant amount of debris, fluid, and fragments of cast-leaf in the device holder [8].…”
Section: Marketing Strategies Of Htp Promotionmentioning
confidence: 99%
“…Moreover, various next-generation products (NGPs), including e-cigarettes and heat-not-burn tobacco products, have been recently introduced in global markets [3,4]. These NGPs can potentially reduce the harms associated with tobacco use because of their reduced yields of toxicants, which is attributable to the generation of aerosols without combusting tobacco leaves [5,6], but the effects of long-term use of these NGPs on human health remain controversial [7,8] despite previous non-clinical [9][10][11][12] and clinical studies [13][14][15]. Epidemiological analysis could be one of the solutions to estimate the realistic risk of the use of such products, but several years would be needed to reach a conclusion.…”
Section: Introductionmentioning
confidence: 99%